Impact of feed raw material to climate and eutrophication impacts of Finnish rainbow trout farming and comparisons on climate impact and eutrophication between farmed and wild fish - Silvenius, Frans; Grönroos, Juha; Kankainen, Markus; Kurppa, Sirpa; Mäkinen, Timo; Vielma, Jouni (Elsevier, 2017)
This study presents environmental impacts of rainbow trout production in Finland, when different raw materials for feed are used. The scenarios under consideration in this study are the present scenario, feed composition in 2009 and scenarios where Baltic herring is used as feed raw material resulting in nutrient circulation in the Baltic Sea area. The system boundaries included production of fish feed and feed raw materials and transports of them. Also considered were hatcheries, fish farming, fish processing and packaging, but these factors were assumed to be the same for all the scenarios. The environmental impacts considered were climate impact and aquatic eutrophication. According to the results, the present eutrophication impact of rainbow trout fillet is 40 kg PO4-eq/ton, when economic allocation was used between fillet and by-products of gutting and filleting. The eutrophication impact of the rainbow trout product chain in 2009 and 2016 were the same: the higher canola oil content increased eutrophication impact as much as the impact was reduced by lower phosphorus and nitrogen emissions of the fish farming stage during years 2009 - 2016. If all the fish-based raw materials for feed are replaced with Baltic Herring, the total eutrophication impact would be 48 kg PO4- eq/ton, when using 2009 feed formulations, but when using 2016 feed formulations the impact would be only 5 kg PO4-eq/ton because of lower fish raw material contents. The fuel consumption used when catching the Baltic herring capturing is about the same as catching the raw materials of fish meal and fish oil from the oceans, so changing the raw material from ocean-based fish to Baltic herring does not have an effect on climate impact of rainbow trout. Also the substitution of fish oil for canola oil does not cause major changes in climate impact. Scenarios where fish are caught and used directly for human consumption show that even more nutrients are omitted from the Baltic Sea in relation to the obtained amount of fish fillet and the climate impact is also lower than in farmed rainbow trout, but uncertainty with regard to the results is high because of limited fishing fuel consumption data. Nevertheless it is not likely that the Finnish consumption of domestic small caught fish, like Baltic herring, will increase because consumer behavior has changed and people prefer to eat salmonids or other fillet-size fish instead. Allocation was found to be critical when calculating environmental impacts of seafood products and in this study economic allocation was preferred. One major question, which was not concerned, is that how to take into account local impacts of fish farming, because life-cycle assessment (LCA) is known to be a limited method for assessing local environmental impacts. That is essential when considering production licenses for fish cultivation in the Baltic Sea.
Keywords: climate impact; nutrient recirculation; Itämeri; kirjolohi; rehevöityminen; ympäristövaikutukset; ravinnekierto; elinkaarianalyysi; Oncorhynchus mykiss; eutrophication; Baltic sea; life cycle analysis; nutrient cycling in ecosystems; ilmastovaikutukset